The Influence of Working Capital and Sales Growth on Net Profit at PT Sido Muncul Tbk (Case Study on the Indonesian Stock Exchange for the 2018-2023 Period) - Neng Anis Safitri; Yuyun Yuniati Yuningsih (Formosa Journal of Social Sciences (FJSS), 2024)
Working capital is a tool to measure a company's ability to create value for investors through the profits it produces. Net profit is a ratio to determine the amount of net profit that has been obtained by the company. Based on this, the author gave the title of this research, namely: "The influence of capital work and sales growth towards net profit for the 2018-2023 period". This research aims to: (1) how working capital, sales growth and net profit at PT Sido TBK appear for the 2018-2023 period. (2) what is the effect of working capital on net profit at PT Sido appears TBK for the 2018-2023 period. (3) how does sales growth affect net profit at PT Sido appears TBK for the 2018-2023 period. (4) what is the influence of working capital and sales growth on net profit at PT Sido appears TBK 2018-2023. The method used in this research is descriptive - associative with an ex-fost facto approach. The data collection method used is documentation. and sampling using non-probability sampling. The data source used is secondary data with the type of data used is quantitative data. The statistical data testing method uses the t statistical test with a significance level of 0.05 and the f test with a significance of 0.010 using the SPSS 26 for Windows program. The research results show that working capital has a negative effect on net profit with a calculated t value of 0.550 and a significance value of 0.05 and a correlation value of 0.079, which means the level of relationship has a negative effect